O direito à saúde e a política nacional de atenção oncológica: uma análise a partir da crescente judicialização dos medicamentos antineoplásicos - Silva, Francisco Livanildo da (2012)
The 1988 Federal Constitution of Brazil by presenting the catalog of fundamental rights and guarantees (Title II) provides expressly that such rights reach the social, economic and cultural rights (art. 6 of CF/88) as a means not only to ratify the civil and political rights, but also to make them effective and practical in the life of the Brazilian people, particularly in the prediction of immediate application of those rights and guarantees. In this sense, health goes through condition of universal right and duty of the State, which should be guaranteed by social and economic policies aimed at reducing the risk of disease and other hazards, in addition to ensuring universal and equal access to actions and services for its promotion, protection and recovery (Article 196 by CF/88). Achieving the purposes aimed by the constituent to the area of health is the great challenge that requires the Health System and its managers. To this end, several policies have been structured in an attempt to establish actions and services for the promotion, protection and rehabilitation of diseases and disorders to health. In the mid-90s, in order to meet the guidelines and principles established by the SUS, it was established the Política Nacional de Atenção Oncológica PNAO, in an attempt to sketch out a public policy that sought to achieve maximum efficiency and to be able to give answers integral to effective care for patients with cancer, with emphasis on prevention, early detection, diagnosis, treatment, rehabilitation and palliative care. However, many lawsuits have been proposed with applications for anticancer drugs. These actions have become very complex, both in the procedural aspects and in all material ones, especially due to the highcost drugs more requested these demands, as well as need to be buoyed by the scientific evidence of these drugs in relation to proposed treatments. The jurisprudence in this area, although the orientations as outlined by the Parliament of Supreme Court is still in the process of construction, this study is thus placed in the perspective of contributing to the effective and efficient adjudication in these actions, with focus on achieving the fundamental social rights. Given this scenario and using research explanatory literature and documents were examined 108 lawsuits pending in the Federal Court in Rio Grande do Norte, trying to identify the organs of the Judiciary behave in the face of lawsuits that seeking oncology drugs (or antineoplastic), seeking to reconcile the principles and constitutional laws and infra constitutional involving the theme in an attempt to contribute to a rationalization of this judicial practice. Finally, considering the Rational Use of health demands and the idea of belonging to the Brazilian people SUS, it is concluded that the judicial power requires ballast parameters of their decisions on evidence-based medicine, aligning these decisions housing constitutional principles that the right to health and the scientific conclusions of efficacy, effectiveness and efficiency in oncology drugs, when compared to the treatments offered by SUS